2020
DOI: 10.1111/evo.14143
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and morphological patterns underlying carnivoran body shape diversity

Abstract: The diversity of body shapes is one of the most prominent features of phenotypic variation in vertebrates. Biologists, however, still lack a full understanding of the underlying morphological components that contribute to its diversity, particularly in endothermic vertebrates such as mammals. In this study, hypotheses pertaining to the evolution of the cranial and axial components that contribute to the diversity of carnivoran body shapes were tested. Three trends were found in the evolution of carnivoran body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
(174 reference statements)
2
14
0
Order By: Relevance
“…Also unsurprisingly, the most statistically significant findings were among the Musteloidea—the lineage that spans both the greatest dietary diversity and body size range in the order. Therefore, musteloids have proven to be interesting as an example of myological diversity that is consistent with the diversity observed in other morphological features of this clade (Law, 2019, 2021). Similarly, interesting observations might be found within Ursids with the addition of the durophagous giant panda ( A. melanoleuca ) to the dataset.…”
Section: Discussionsupporting
confidence: 72%
“…Also unsurprisingly, the most statistically significant findings were among the Musteloidea—the lineage that spans both the greatest dietary diversity and body size range in the order. Therefore, musteloids have proven to be interesting as an example of myological diversity that is consistent with the diversity observed in other morphological features of this clade (Law, 2019, 2021). Similarly, interesting observations might be found within Ursids with the addition of the durophagous giant panda ( A. melanoleuca ) to the dataset.…”
Section: Discussionsupporting
confidence: 72%
“…Body shape also plays a determinant role at multiple physiological levels; for example, in describing the space available for accommodating major organ systems 4 , 5 , and body surface area for heat exchange 6 , 7 . Because different environments and behaviours place different demands on the functional mechanics and physiologies of organisms, it is expected that body proportions should vary across animals occupying different ecological niches 8 14 . However, modification of body size and shape by ecological pressures may also be constrained by other factors, notably phylogenetic history and the ecological trajectory of evolutionary change 3 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the universal potential for natural selection to act upon body shape, it is not surprising that many studies have sought to investigate associations between body proportions and ecological niche occupation 8 14 . While these studies have regularly identified important trends in the evolution of body proportions 8 14 , they have tended to focus on individual taxonomic or ecological groups, or on an individual aspect of body shape. However, to our knowledge, no study has systematically investigated allometric patterns or ecological differences in whole-body proportions across a highly diverse sample of extinct and extant tetrapods.…”
Section: Introductionmentioning
confidence: 99%
“…Friedman, Price, & Wainwright, 2021;Ruff, 1991;Schluter, 1996aSchluter, , 2000Smith, Nelson-Maney, Parsons, Cooper, & Albertson, 2015). A major axis of this morphological variation is body elongation, which occurs within reptiles (Bergmann & Irschick, 2012;Losos, 2009;Wiens & Slingluff, 2001), carnivorous mammals (Law, 2019(Law, , 2021, and fishes (S. T.…”
Section: Introductionmentioning
confidence: 99%
“…Friedman, Price, & Wainwright, 2021;Ruff, 1991;Schluter, 1996aSchluter, , 2000Smith, Nelson-Maney, Parsons, Cooper, & Albertson, 2015). A major axis of this morphological variation is body elongation, which occurs within reptiles (Bergmann & Irschick, 2012;Losos, 2009;Wiens & Slingluff, 2001), carnivorous mammals (Law, 2019(Law, , 2021, and fishes (S. T. Friedman et al, 2020;Price et al, 2019;Ward & Mehta, 2010). Within fishes, elongation of the body is associated with a major ecomorphological divergence, the benthic-pelagic axis.…”
Section: Introductionmentioning
confidence: 99%